ANALYSIS OF THE JUDGE’S DECISION IN THE CRIMINAL ACT OF EMBEZZLEMENT COMMITTED BY A CASHIER (ANALYSIS OF THE MEDAN DISTRICT COURT DECISION NUMBER 1207/PID.B/2025/PN MDN) - Tedi Permadi; Nelvitia Purba (CV. Barokah Publsiher, 2026)
Based on the results of the study, it shows that the legal regulations related to the crime of embezzlement committed by the cashier are regulated in Article 374 of the Criminal Code concerning the Crime of Embezzlement with Aggravation and are threatened with a maximum imprisonment of five years. The proof of the elements of the crime of embezzlement committed by the cashier in the Medan District Court Decision Number 1207 / Pid.B / 2025 / PN Mdn is appropriate, namely the proof of the elements has been proven based on evidence of witness testimony, evidence of the defendant's testimony, and evidence of indications. The judge's consideration of the case of the crime of embezzlement committed by the cashier in the Medan District Court Decision Number 1207 / Pid.B / 2025 / PN Mdn is appropriate because it is in accordance with Article 184 of the Criminal Procedure Code.